1971
DOI: 10.1055/s-0028-1094141
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanism of Pentobarbital-Induced Glucose Intolerance

Abstract: The disposal of intravenous glucose (%/min ± SE) was markedIy delayed in rats anesthetized with 50 mg/kg of intraperitoneal sodium pentobarbital (K=2.14 ± 0.23) compared to conscious litter mates (K=3.95 ± 0.21). There were no differences in fasting plasma glucose concentrations or in the insulin response to administered glucose. Diaphragms and epididymal fat pads removed from anesthetized animals differed in their vitro response to glucose and insulin only by a small (10%), but significant (p <0.05), decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1973
1973
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…There was no statistically significant difference between the results obtained for the treated obese and control lean animals although the values obtained for the former tended to be slightly higher. The removal of glucose from the blood was slower than is normally observed and we ascribe this to the fact that for these tests the animals were kept under pentobarbital anaesthesia (Davidson, 1971).…”
Section: Resultsmentioning
confidence: 94%
“…There was no statistically significant difference between the results obtained for the treated obese and control lean animals although the values obtained for the former tended to be slightly higher. The removal of glucose from the blood was slower than is normally observed and we ascribe this to the fact that for these tests the animals were kept under pentobarbital anaesthesia (Davidson, 1971).…”
Section: Resultsmentioning
confidence: 94%
“…anesthesia, since pentobarbital was shown not to alter the metabolic parameters tested herein (constant rate for glucose disappearance [ K ITT ], fasting glycemia, insulinemia, and free fatty acids) in comparison with conscious animals (20) or insulin responses to glucose (21). At the end of the experiments, the rats were killed by an intracardiac overdose of pentobarbital, except when heart puncture was performed to collect blood.…”
Section: Methodsmentioning
confidence: 99%
“…We found that the arginine-stimulated IRG "secretion" from A cells in the STZ-treated dogs did not differ from the The secretion of IRG stimulated by insulin-induced hypoglycemia is considered to be influenced by several factors including the degree of hypoglycemia and the rate of decrease in blood glucose (Gerich et al, 1974). We found that the rate of the fall and the nadirs of blood glucose levels in the It is well known that anaesthesia may affect pancreatic hormonal secretion and glucose metabolism (Davidson, 1971;Bailey and Flatt, 1980). We evaluated the hormonal secretions in the STZ-treated dogs under the same conditions as the control dogs which showed significant insulin and glucagon secretion in response to stimuli.…”
Section: Discussionmentioning
confidence: 66%